Energy Storage: High‐Performance High‐Loading Lithium–Sulfur Batteries by Low Temperature Atomic Layer Deposition of Aluminum Oxide on Nanophase S Cathodes (Adv. Mater. Interfaces 17/2017). Issue 17 (8th September 2017) - Meng, Xiangbo; Liu, Yuzi; Cao, Yanqiang; Ren, Yang; Lu, Wenquan; Elam, Jeffrey W.
Abstract : Lithium–sulfur batteries suffer severe capacity fade from sulfur dissolution. To combat this problem, Jeffrey W. Elam and co‐workers coated the surface of nanophase S with Al2 O3 via low‐temperature atomic layer deposition (ALD), as described in article number1700096 . The ALD of Al2 O3 evolves with thickness—from dispersed nanoparticles, to porous films, to continuous coatings. The result is high‐performance Li–S batteries at high S loading.